Eyes on the Future: ReciclaMente - Galio Jáckson Teixeira; Sadalla, Beatriz de Aragão; Consoni, Flávia L.; Conceição Geovana Ketllyn Almeida (Technical and Scientific Journal Green Cities, 2025)
ABSTRACT: Objective – This study presents the structure and methodology of the ReciclaMente subproject, part of the Eyes on the Future program, developed in collaboration between the University of Campinas (UNICAMP) and E.E. Dr. Telêmaco Paioli Melges (Campinas-SP). The central objective is to demonstrate how collaborative activities related to Sustainable Development Goal (SDG) 12 – Responsible Consumption and Production – can contribute to the formation of transformation agents within the school community. Methodology – The research employed the Active Learning Methodology and the Interdisciplinary Action Methodology (MAI), ensuring that the subproject’s activities were interdisciplinary and cooperative, valuing students’ reflections on their local reality. Biweekly workshops, practical activities in Youth Clubs, and visits to UNICAMP were developed, integrating teaching, research, and outreach. Originality/relevance – The study highlights the potential of environmental education in primary education by connecting SDGs to school life. The research emphasizes the importance of educational initiatives that encourage student leadership, promote sustainable consumption, and foster proper solid waste management. Results – The main results include active student participation in analyzing and proposing school changes; implementation of selective waste collection and separation; contact with professionals involved in waste collection; and immersion in the university environment through the Eyes on the Future Journey. These activities demonstrated the relevance of interdisciplinary pedagogical strategies for environmental awareness and social transformation. Theoretical/methodological contributions – The research reinforces the importance of interdisciplinarity in environmental education and geoscience teaching, using participatory methodologies to bring students closer to socio-environmental realities. The study also contributes to the curricularization of university outreach, promoting interactions between schools and universities. Social and environmental contributions – ReciclaMente fosters sustainable practices within the school environment, raising awareness about consumption and proper waste disposal. Additionally, it strengthens the connection between schools, universities, and communities, encouraging student engagement in building more sustainable cities.